Trends of traffic fatalities and DNA analysis in traffic accident investigation. (July 2019) - Taki, Takashi; Machida, Mitsuyo; Shimada, Ryo
Abstract: Although the number of traffic accidents in Japan decreases each year, little is known about the annual trends of various types of traffic accidents. In this study, we used public domain to examine annual trends in the number of fatalities caused by traffic accidents by age and type of transportation. We found that such trends differed by age group and type, and that the number of deaths due to certain types of traffic accidents is increasing. Identification by DNA analysis is now widely used in traffic accident investigations, but the public is largely unaware of the components of DNA that are investigated and the way in which the analysis is conducted. For this reason, we introduced an outline of the DNA analysis that is conducted in the traffic accident investigations and present several cases in which DNA analysis has been effectively utilized in such investigations. Highlights: Fatal traffic accidents are decreasing, but the speed of this decline differs by age group and transportation type. Current DNA analysis methods are described. DNA analysis is widely used for individual identification in traffic accident investigations. Several measures must be taken to reduce fatal traffic accidents in Japan.